Technical steps of open radical cystectomy and orthotopic neobladder to achieve the goals of "minimally invasive surgery"? - Anil Mandhani; Anand Dharaskar; Rakesh Kapoor (Indian Journal of Urology, 2010)
Technical modifications in open approach to radical cystectomy and orthotopic neobladder (ONB), that is, Pfannenstiel incision, single urethral catheter, internal splint, and extraperitonealization of the ONB were done in 36 patients. Median operative time was 300 (240-360) min. Median time to move the bowel and start of oral intake was 4 days (2-8) days. Major complications occurred in 3 (8.33%) patients. Mean postoperative pain score was 2 (1-4). These modifications in open radical cystectomy resulted in better cosmesis, less pain, and more comfort to the patients as they had to carry one urobag for 3 weeks.